Censorship: Slowdown (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2024)
WARNING severity censorship detected in Kazakhstan. Data sourced from CensoredPlanet.
Censorship Incident ID: KZ-2024-0003. Severity: warning. Confidence: 75%